Effects of a mindfulness-based interventions on stress, burnout in nurses: a systematic review and meta-analysis - Wang, Qi; Wang, Fang; Zhang, Shurong; Liu, Chaofan; Feng, Yue; Chen, Junzhu (Frontiers in Psychiatry, 2023)
Background Stress in the healthcare environment causes negative effects in nurses such as burnout, anxiety, and depression. The COVID-19 pandemic has resulted in increased pressure on medical staff globally, highlighting the potential benefits of mindfulness-based interventions in reducing nurses’ stress levels. Despite numerous studies exploring the effect of mindfulness-based training on nurses, the results remain inconclusive. Objective To systematically evaluate the impact of mindfulness training on nurse’s performance and increase the certainty of existing evidence. Methods This study searched various databases, including EBSCO, Embase, Web of Science, PubMed, ProQuest, Scopus, Cochrane Online Library, Wanfang, SinoMed, CNKI, and VIP, for randomized controlled trials on the impact of mindfulness-based interventions for nurses up until 02 December 2022. Two investigators independently screened and extracted data from the articles, while also assessing the risk of bias. The data was analyzed using RevMan 5.4 software. Results This review identified 15 studies out of the 2,171 records retrieved, consisting of a total of 1,165 participants who were randomized. Post-intervention analysis provided very-low certainty evidence of moderate effectiveness of mindfulness-based training in reducing stress [standardized mean difference (SMD) = −0.81; 95% confidence interval (CI) = −1.11 to −0.52], with no significant effect on anxiety (SMD = −0.30; 95% CI = −0.72 to 0.13) or depression (SMD = −0.24; 95% CI = −0.55 to 0.07). However, the training was effective in reducing burnout, as demonstrated by the lower scores for emotional exhaustion (SMD = −4.27; 95% CI = −5.94 to −2.59) and depersonalization (SMD = −2.89; 95% CI = −4.24 to −1.54) and higher scores for personal accomplishment (SMD = 2.81; 95% CI = 0.12 to 5.50). There was a sustained improvement in stress levels in the short-term (≤3 months), with delayed benefits for burnout. However, only two studies were available for later follow-ups, and there was no significant evidence of long-term effects. Conclusion Mindfulness-based training may be a viable intervention for improving the psychological wellbeing of nurses, including reducing stress, burnout. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023387081.